Analysis of the Impact of Social Media Usage on the Effectiveness of University Students' Study Time - Wahdaniyati, Mirna; Astuti, Eka Puji; Dwiyanti, Malini Putri; Gunawan, Gunawan (Indonesian Publication Center, 2025)
This study aims to analyze the influence of social media usage on the effectiveness of university students' study time by examining usage intensity, content types, and perceived impacts on academic focus. A descriptive quantitative approach was employed, utilizing a Likert-scale survey distributed to 61 active social media users. Data were analyzed using descriptive statistics to identify usage patterns and behavioral trends. The results indicate that the majority of respondents were physics education students (aged 18–21), with a female predominance of 83.6%. TikTok emerged as the most widely used platform (50,8%), followed by WhatsApp (29,5%) and Instagram (18,0%), with a typical daily usage duration of 1–3 hours (44,3%). A key finding reveals that 93% of respondents acknowledged that social media significantly affects their study focus, primarily through entertainment-related distractions (45,9%) and increased academic procrastination. Although 72,1% of students access social media during leisure time, usage during study hours and before sleep persists, negatively impacting rest quality and concentration. The study concludes that social media serves a dual role as both a learning resource and a potential hindrance to study efficiency. Consequently, strict time management and self-regulation in content consumption are essential to mitigate its adverse effects on academic performance.